2004
DOI: 10.1007/s11745-004-1220-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fish oil supplementation in lactation: Effect on visual acuity and n−3 fatty acid content of infant erythrocytes

Abstract: Studies on formula-fed infants indicate a beneficial effect of dietary DHA on visual acuity. Cross-sectional studies have shown an association between breast-milk DHA levels and visual acuity in breast-fed infants. The objective in this study was to evaluate the biochemical and functional effects of fish oil (FO) supplements in lactating mothers. In this double-blinded randomized trial, Danish mothers with habitual fish intake below the 50th percentile of the Danish National Birth Cohort were randomized to mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
1
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 30 publications
(46 reference statements)
5
117
1
8
Order By: Relevance
“…Erythrocytes (RBC) were isolated from heparinized blood samples, washed, and kept at -80°C for later analysis, as described elsewhere (Lauritzen et al 2004). The content of specific fatty acids was calculated as area % of the specific fatty acid relative to the total identified chromatogram area (FA %), which is almost equivalent to % by weight.…”
Section: Rbc Fatty Acid Analysesmentioning
confidence: 99%
“…Erythrocytes (RBC) were isolated from heparinized blood samples, washed, and kept at -80°C for later analysis, as described elsewhere (Lauritzen et al 2004). The content of specific fatty acids was calculated as area % of the specific fatty acid relative to the total identified chromatogram area (FA %), which is almost equivalent to % by weight.…”
Section: Rbc Fatty Acid Analysesmentioning
confidence: 99%
“…Around 80% of the infants completed the mental follow-up measures reported in the present paper, resulting in a power to show a difference between the randomized groups of around 0.6 SD of functional outcome. The details of the study design and recruitment procedure, which have been reported elsewhere [29], are described briefly here.…”
Section: Participants Trial and Supplementsmentioning
confidence: 99%
“…All drop-outs were due to choices made by the participants (as explained in [29]), none of the mothers were excluded for lack of compliance with supplements or the breast-feeding request. During this period 107 mothers complied with the criteria for exclusive breastfeeding.…”
Section: Participants Trial and Supplementsmentioning
confidence: 99%
See 2 more Smart Citations